2004
DOI: 10.1079/phn2003536
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of middle-aged women at 65–71°N in relation to dietary intake and exposure to ultraviolet radiation

Abstract: Objective: To determine the vitamin D status of middle-aged women living in the Norwegian arctic and its relationship with vitamin D intake and exposure to ultraviolet (UV) radiation. Design: Cross-sectional study. Conclusions: Increased ingestion of marine food items that provide vitamin D should be promoted and further studies should be carried out to investigate vitamin D status in arctic populations in relation to both UV exposure and traditional food sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
145
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(168 citation statements)
references
References 30 publications
18
145
4
1
Order By: Relevance
“…In a northern area of Norway (69°N), high intake of cod liver oil substantially reduced the expected seasonality of serum 25(OH)D in the population [17]. Despite consumption of foods containing substantial amounts of vitamin D, serum 25(OH)D levels generally are lower in residents of northern areas of Norway [18] and Finland [19]. Consistent with this finding, one more recent study in Sweden reported that incidence rates of type 1 diabetes increased with increasing latitude [20], suggesting that the apparent reversal in incidence rates compared with expectation may be disappearing with time there.…”
Section: Discussionmentioning
confidence: 99%
“…In a northern area of Norway (69°N), high intake of cod liver oil substantially reduced the expected seasonality of serum 25(OH)D in the population [17]. Despite consumption of foods containing substantial amounts of vitamin D, serum 25(OH)D levels generally are lower in residents of northern areas of Norway [18] and Finland [19]. Consistent with this finding, one more recent study in Sweden reported that incidence rates of type 1 diabetes increased with increasing latitude [20], suggesting that the apparent reversal in incidence rates compared with expectation may be disappearing with time there.…”
Section: Discussionmentioning
confidence: 99%
“…prevalence of vitamin D deficiency is high in the winter and spring months. Thus, although intake alone at current levels may not yield very high levels of vitamin D in circulation, it is an important factor in preventing vitamin D deficiency in winter months, as shown in other studies (16)(17)(18)42). Finally, because we do not have detailed information about sun exposure for participants in either cohort, we used state of residence divided by geographic latitude as a limited proxy for potential solar UVB exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Additional sources are natural dietary content, vitamin food fortification and supplements. The latitude of geographical location is of importance for obtaining sufficient sunlight for the synthesis of active vitamin D. Seasonal variation in vitamin D levels have been illustrated in the Nordic countries [14,15] and in the United Kingdom where high prevalence of deficient vitamin D levels have been found during winter and spring [16]. In the Nordic countries, exposure to the sun is below critical level for half of the year.…”
Section: Introduction and Objectivesmentioning
confidence: 99%